Mobile fitness and weight management apps: protocol for a quality evaluation - Milne-Ives, M; Lam, C; van Velthoven, M; Meinert, E (JMIR Publications, 2020)
Background: Obesity is a contributing factor for many noncommunicable diseases and a growing problem worldwide. Many mobile apps have been developed to help users improve their fitness and weight management behaviors. However, the speed at which apps are created and updated means that it is important to periodically assess their quality.